A new species of Croton sect. Geiseleria (Euphorbiaceae) from Brazil, supported by macro- and micromorphological data - Da Silva, Marcos José; Sodré, Rodolfo Carneiro; Alonso, Alexandre Antonio; Dos Santos, Igor Soares (Phytotaxa, 2024)
Taxonomic studies on the genus Croton in the Midwest region of Brazil enabled the analysis of about 700 collections from all over the country. Three of these collections were identified as a new species, Croton piriquetifolius, which is described and illustrated here. We also give a preliminary evaluation of its conservation status, provide data on flowering and fruiting seasons, geographic distribution environmental preferences, as well as its systematic position. The new species is compared macro- and micromorphologically with C. adamantinus, C. glandulosus and C. eremophilus, with which it resembles or has been confused in herbaria. Morphological (e.g., presence, shape, and location of the acropetiolar nectaries, presence, and distribution of glands on stipules, presence, and size of pedicel on pistillate flower, integrity of styles, type, and location of trichomes) and anatomical (e.g., disposition of the stomata, contour of petiole and midrib, organization of vascular bundles, type of mesophyll, and types of trichomes) characters serve to differentiate the species studied.